2012
DOI: 10.1111/j.1365-2672.2012.05283.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of ceftazidime-resistant Acinetobacter baumannii clonal complex 92 in Korea

Abstract: Aims:  This study was performed to describe the epidemiological traits of ceftazidime‐resistant Acinetobacter baumannii clinical isolates from Korea. Methods and Results:  Antimicrobial susceptibilities were determined by disk diffusion assay. PCR experiments were performed to detect genes encoding extended‐spectrum β‐lactamases and metallo‐β‐lactamases. Detection of ISAba1 upstream of the blaADC gene was also performed by PCR amplification. The genetic organization of the blaPER‐1 gene was investigated by PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…baumannii isolates in Latin America belong to CC113, in contrast with studies in many countries around the world that showed that A . baumannii harboring OXA-23 isolates were related to specific clones belonging to CC92 [ 35 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…baumannii isolates in Latin America belong to CC113, in contrast with studies in many countries around the world that showed that A . baumannii harboring OXA-23 isolates were related to specific clones belonging to CC92 [ 35 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…PER-type ESBL is the most commonly found ESBL in A. baumannii [33, 34], but production of VEB-type ESBL and CTX-M-type ESBL, which is the most common ESBL in E. coli , has also been reported [35, 36]. …”
Section: Mechanisms Of Antimicrobial Resistancementioning
confidence: 99%
“…62,63 In addition to ADC β-lactamase, A. baumannii may also produce extended-spectrum β-lactamase (ESBL), which also leads to cephalosporin resistance. [64][65][66][67]…”
Section: Cephalosporinsmentioning
confidence: 99%